2019
DOI: 10.1002/jhbp.681
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermic perfusion hepatectomy for unresectable liver cancer: A single‐center experience

Abstract: Background:The resection of liver tumors that involve the hepatic veins adjacent to the vena cava or hepatic hilum is technically challenging. We present our surgical techniques and the long-term outcome of five patients with conventionally unresectable tumors. Methods: Five patients with conventionally unresectable tumors were successfully treated by "ex-situ liver resection" and "in-situ and ante-situm hypothermic liver perfusion" under total vascular exclusion and venovenous bypass. Results: These approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Previous studies have suggested that greater than 5% hypertrophy in the intended remnant improves outcomes after PVE [19]. Other approaches to mitigate the risk of PHLF include “associating liver partition and portal vein ligation for staged hepatectomy” (ALPPS) [21, 22], radiation lobectomy [23, 24], liver venous deprivation [18, 25], and hypothermic perfusion [26].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that greater than 5% hypertrophy in the intended remnant improves outcomes after PVE [19]. Other approaches to mitigate the risk of PHLF include “associating liver partition and portal vein ligation for staged hepatectomy” (ALPPS) [21, 22], radiation lobectomy [23, 24], liver venous deprivation [18, 25], and hypothermic perfusion [26].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the cases operated in this study was mainly indicated for locally advanced hepatobiliary malignancies with a substantial proportion of patients with single bulky tumor that had macrovascular invasion, or adjacent organ invasion. Such tumor high tendency to invade major intrahepatic vasculature often demanded portal vein or hepatic vein reconstruction to achieve a R0 resection, 23,24 or in the case of hilar cholangiocarcinoma when portal vein resection was often needed for tumor clearance 25 due to its proximity to portal vein at the biliary confluence. Rare tumors, for example, leiomyosarcoma of the retrohepatic vena cava with juxtaposition to the liver (Fig.…”
Section: Discussionmentioning
confidence: 99%